Polyphosphate as a Target for Interference With Inflammation and Thrombosis - Mailer, Reiner K. W.; Hänel, Lorena; Allende, Mikel; Renné, Thomas (Frontiers in Medicine, 2019)
Activated platelets and mast cells expose the inorganic polymer, polyphosphate (polyP) on their surfaces. PolyP initiates procoagulant and proinflammatory reactions and the polymer has been recognized as a therapeutic target for interference with blood coagulation and vascular hyperpermeability. PolyP content and chain length depend on the specific cell type and energy status, which may affect cellular functions. PolyP metabolism has mainly been studied in bacteria and yeast, but its roles in eukaryotic cells and mammalian systems have remained enigmatic. In this review, we will present an overview of polyP functions, focusing on intra- and extracellular roles of the polymer and discuss open questions that emerge from the current knowledge on polyP regulation.